Tourism Education and Career Readiness: A Case Study of Himachal Pradesh Government Schools - Raj, Shiv; Sharma, Suman (Program Studi Pendidikan Pariwisata, Universitas Pendidikan Indonesia, 2023)
Tourism education is recognized as a vital component in preparing students for careers within the dynamic hospitality and tourism industry. This research investigates the role of tourism education in shaping career readiness among students in Himachal Pradesh Government Schools. The research explores the current state of tourism education in these schools, analysing curriculum design, teaching methodologies, and the integration of practical experiences. Additionally, the study scrutinizes the perceptions of students, educators, and industry professionals regarding the effectiveness of existing programs in fostering career readiness. Through surveys, interviews, and document analysis, the research aims to identify strengths, weaknesses, and potential areas for improvement in the tourism education offered by Himachal Pradesh Government Schools. The findings of this study contribute valuable insights to the broader discourse on tourism education and its role in shaping career readiness, particularly in the context of government schools situated in tourist-centric regions. Ultimately, the research aims to inform educational strategies that better equip students with the skills and knowledge necessary for successful and fulfilling careers in the dynamic field of tourism.